A study of anxiety and depression in benign breast disease - Vivek Srivastava; Rakesh Kumar Meena; Mumtaz A Ansari; Dheeraj Kumar; Anand Kumar (Wolters Kluwer Medknow Publications, 2020)
Background: To compare the prevalence of anxiety and depression levels in patients with benign breast disease (BBD) and healthy individuals using Hospital Anxiety and Depression Scale (HADS) and Brief Patient Health Questionnaire (BPHQ). Methods: This study includes 100 patients who were clinically suspected of having BBDs and were matched against 100 healthy age-matched controls from June 2016 and July 2018. The diagnosis of BBD was established on the basis of ultrasonography, fine needle aspiration cytology, and/or histopathology. For the diagnosis of anxiety and depression, BPHQ was used and the level of anxiety and depression was measured using the HADS. The questionnaire at both prediagnosis and at follow-up assessment after 3 months was done. Results: On comparing anxiety and depression using BPHQ score among cases and controls, both were significantly associated with cases than controls (P < 0.001 and P = 0.0016, respectively). On comparing anxiety and depression using HADS score, there was a significant difference (median) in both anxiety and depression level between cases and controls (P < 0.001 and P < 0.001, respectively). After 3 months of follow-up, there was a significant improvement in anxiety and depression scores by both BPHQ (P = 0.007 and P = 0.0016) and HADS (P < 0.001 and P < 0.001). The 3-month follow-up data showed a significant improvement in BPHQ (depression) score in patients with breast lump and mastalgia (P = 0.001 and P = 0.008). The HADS (anxiety score) showed significant improvement in patients presenting with diseases/aberrations other than fibroadenoma while the HADS (depression) score showed a significant improvement in all except fibroadenosis present either alone or along with fibroadenoma. The HADS (depression) score showed a significant improvement in fibroadenoma, others group, breast lump, and mastalgia (P = 0.040, P = 0.005, P < 0.001, and P = 0.025, respectively). Conclusion: Indian female patients who present with BBDs are also affected by anxiety and depression.